Risk factors for infection in external ventricular drains - Santos Araujo, Audrey Beatriz; Gusmão, Sebastião; Magaldi, Marcelo; Vanderlei, Alander Sobreira; Ribeiro Cambraia, Marina Brugnolli (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2013)
Objective: The present study aims to define the main risk factors for infection in EVD implants performed in a public tertiary hospital in Belo Horizonte, Brazil. Method: The present study performed a retrospective review of 137 cases of EVD implants in 107 patients from January 2006 to December 2008. Of these cases, 25 patients had to be re-operated, totally 141 implanted shunts. Results: Forty-eight (45%) patients were male and 59 (55%) were female. The age ranged from 6 to 86 years of age (52.12 ± 15.51 years). The incidence of EVD-related infection was 32.7%, while the device permanence varied from 2 to 54 days (mean of 10 days). The EVDs that were maintained for more than 9.5 days, as well as the device changes proved to be statistically significant factors for cerebrospinal fluid (CSF) infection (p < 0.001). Antibiotic prophylaxis did not change the infection rate (p = 0.395). Conclusions: Risk factors for EVD infection included a continuing EVD permanence that lasted for more than 9.5 days and device changes. The present study concluded that there is no advantage for antibiotic prophylaxis regarding CSF infection with EVD implants.
Keywords: Infection; cerebral ventriculitis; risk factors; antibiotic prophylaxis; hydrocephalus